Highly-oriented proton conducting BaZr0.9Y0.1O3−x ceramic thin films prepared by chemical solution deposition. Issue 7 (July 2022) - Xiao, Yao; Waser, Rainer; Schneller, Theodor
Abstract: In this work, the parameters for the formation of 10% yttrium-doped barium zirconate (BZY) thin films were investigated systematically using the low-cost and scalable chemical solution deposition method. By modifying the chemistry of the precursor solution and applying different thermal treatment schedules, the key parameters of controlling microstructure and growth orientation were unraveled. Films with porous and lamellar, granular, and dense columnar structures, respectively, were obtained at a relatively low annealing temperature (950 ℃). Particularly, the film with a highly (200) preferred orientation was attained by employing a seed layer approach, in combination with a butyrate-based precursor coating solution. The decomposition of the precursors was surveyed through thermal analysis. The in-plane conductivity of BZY films was investigated by electrochemical impedance spectroscopy and the corresponding activation energy was evaluated. The relationship between microstructures and electrochemical properties was discussed and concluded that the denser BZY film with larger grains shows better performance. Highlights: High (200) oriented Ba(Zr, Y)O3 (BZY) films with dense columnar microstructure were prepared by chemical solution deposition. The average grain size of BZY thin films can reach about 60 nm at a relatively low annealing temperature (950 °C). The nonorthodox butyric acid-based precursor solution shows unique decomposition properties among the precursor solutions. High temperature impedance spectroscopy was applied to evaluate the proton-conducting properties of the BZY thin films.